Poster Presentations 2017
DOI: 10.1136/annrheumdis-2017-eular.3249
|View full text |Cite
|
Sign up to set email alerts
|

SAT0650 [18F]FLUORO-PEG-FOLATE pet: a novel imaging technique to visualize rheumatoid arthritis

Abstract: BackgroundImaging arthritis activity in rheumatoid arthritis (RA) patients using PET macrophage tracers holds promise for both early diagnostics and monitoring response to therapy (1,2). Previously, (R)-[11C]PK11195 has been used, but this macrophage tracer is limited due to high background uptake, especially in bone and bone marrow. Recently, a novel macrophage tracer, [18F]fluoro-PEG-folate, was developed, which showed excellent targeting of the folate receptor beta on activated macrophages in synovial tissu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…PET tracers, developed to visualize TAMs, have been used in rheumatoid arthritis [66,67]. [ 18 F]fluoro-PEG-folate can bind FR-β on the surface of these macrophages.…”
Section: Validation Statementioning
confidence: 99%
See 1 more Smart Citation
“…PET tracers, developed to visualize TAMs, have been used in rheumatoid arthritis [66,67]. [ 18 F]fluoro-PEG-folate can bind FR-β on the surface of these macrophages.…”
Section: Validation Statementioning
confidence: 99%
“…[ 18 F]fluoro-PEG-folate can bind FR-β on the surface of these macrophages. Recently, a first-inhuman study investigated the biodistribution of this tracer and showed high uptake in arthritic joints [67]. To our knowledge, no clinical PET studies using a FR-β tracer to visualize macrophages in the TME in cancer patients have been published yet, however, these studies are of interest, as myeloid cells and TAMs participate in the primary and acquired resistance to IO [65].…”
Section: Validation Statementioning
confidence: 99%